1997
DOI: 10.1530/eje.0.1370490
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of fasting proinsulin in 148 siblings of patients with insulin-dependent diabetes mellitus. Study Group on Childhood Diabetes in Finland

Abstract: Objective: To follow proinsulin immunoreactive material (PIM) in healthy siblings from the time of diagnosis of insulin-dependent diabetes mellitus (IDDM) in the proband, for at least 2 years. Design and methods: The study comprised 148 siblings representing 112 families. The siblings were recruited from the nationwide 'Childhood Diabetes in Finland' study and tested for immunological markers. If a sibling was found positive for islet cell antibodies (ICA) or insulin autoantibodies (IAA), PIM sampling was exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
2
3
0
1
Order By: Relevance
“…The discrepancy with the present observation may relate to the use of random vs fasting values, different hormone and antibody assays, and low numbers both in older studies and our control group. However, it does not invalidate our observation of a(n) (further) increase in proinsulin and PI:C closer to diagnosis, which was also noted by others [14,32,33]. In particular, the use of random hormone levels may lead to more overlapping results between groups tested, but remains the only option to screen large groups of active non-diabetic relatives nationwide.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The discrepancy with the present observation may relate to the use of random vs fasting values, different hormone and antibody assays, and low numbers both in older studies and our control group. However, it does not invalidate our observation of a(n) (further) increase in proinsulin and PI:C closer to diagnosis, which was also noted by others [14,32,33]. In particular, the use of random hormone levels may lead to more overlapping results between groups tested, but remains the only option to screen large groups of active non-diabetic relatives nationwide.…”
Section: Discussionsupporting
confidence: 74%
“…Up to a 500-fold excess of C-peptide did not interfere in the proinsulin assay. Because of high crossreactivity with conversion intermediates [74% for split (32)(33) proinsulin, 65% for des (31,32) proinsulin, 78% for split(65-66) proinsulin and 99% for des(64,65) proinsulin], the assay was considered to measure total proinsulin immunoreactive material [27]. It comprises two separate overnight incubations allowing the monoclonal antibodies used in the assay to compete with IAA (if present in the plasma tested) for binding to proinsulin.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggested that the impaired insulin secretory capacity in the offspring of LADA patients (9) is characterised by a subtle defect in the processing of insulin precursors, unlike in the offspring of patients with type 2 diabetes (34). On the other hand, although hyperproinsulinaemia was not so profound as described in first-degree relatives of patients with type 1 diabetes (13)(14)(15)(16)(17)(18)(19) it supports the concept that LADA has metabolic features typical of classical type 1 diabetes. Moreover, hyperproinsulinaemia was observed only in the offspring of GADA-positive LADA patients, providing further evidence that LADA is a heterogeneous disorder (8,10).…”
Section: Discussionsupporting
confidence: 58%
“…In Finland, an increased PI:C ratio was observed in 11 antibody-positive siblings of persons with type 1 diabetes who exhibited reduced first-phase insulin responses during an intravenous glucose tolerance test (9). Fasting PI-immunoreactive material increased during the 6 months prior to diabetes onset in seven of nine siblings of type 1 diabetes probands who were monitored longitudinally for type 1 diabetes development (28). An elevated random PI:C ratio was also present in Belgian autoantibody positive first-degree relatives in whom type 1 diabetes developed within 11–50 months (10).…”
Section: Discussionmentioning
confidence: 99%